Bacterial overgrowth during treatment with omeprazole compared with cimetidine: a prospective randomised double blind study. Issue 1 (July 1996) - Thorens, J; Froehlich, F; Schwizer, W; Saraga, E; Bille, J; Gyr, K; Duroux, P; Nicolet, M; Pignatelli, B; Blum, A L; Gonvers, J J; Fried, M
Abstract : BACKGROUND: Gastric and duodenal bacterial overgrowth frequently occurs in conditions where diminished acid secretion is present. Omeprazole inhibits acid secretion more effectively than cimetidine and might therefore more frequently cause bacterial overgrowth. AIM: This controlled prospective study compared the incidence of gastric and duodenal bacterial overgrowth in patients treated with omeprazole or cimetidine. METHODS: 47 outpatients with peptic disease were randomly assigned to a four week treatment regimen with omeprazole 20 mg or cimetidine 800 mg daily. Gastric and duodenal juice were obtained during upper gastrointestinal endoscopy and plated for anaerobic and aerobic organisms. RESULTS: Bacterial overgrowth (> or = 10(5) cfu/ml) was present in 53% of the patients receiving omeprazole and in 17% receiving cimetidine (p < 0.05). The mean (SEM) number of gastric and duodenal bacterial counts was 6.0 (0.2) and 5.0 (0.2) respectively in the omeprazole group and 4.0 (0.2) and 4.0 (0.1) in the cimetidine group (p < 0.001 and < 0.01; respectively). Faecal type bacteria were found in 30% of the patients with bacterial overgrowth. Basal gastric pH was higher in patients treated with omeprazole compared with cimetidine (4.2 (0.5) versus 2.0 (0.2); p < 0.001) and in patients with bacterial overgrowth compared with those without bacterial overgrowth (5.1 (0.6) versus 2.0 (0.1); p < 0.0001). The nitrate, nitrite, and nitrosamine values in gastric juice did not increase after treatment with either cimetidine or omeprazole. Serum concentrations of vitamin B12, beta carotene, and albumin were similar before and after treatment with both drugs. CONCLUSIONS: These results show that the incidence of gastric and duodenal bacterial overgrowth is considerably higher in patients treated with omeprazole compared with cimetidine. This can be explained by more pronounced inhibition of gastric acid secretion. No patient developed signs of malabsorption or an increase of N-nitroso compounds. The clinical significance of these findings needs to be assessed in studies with long-term treatment with omeprazole, in particular in patients belonging to high risk groups such as HIV infected and intensive care units patients.